Biocontrol: fighting pests using natural enemies - Part 02 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
After beneficial insects are bred in the laboratory, they are released into fields to fight pests. Is it effective? Manuel Tamo, shares some major successes regarding the control of Maruca vitrata in cowpea in Benin and Niger.